2020
DOI: 10.21873/anticanres.14213
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Large Cell Neuroendocrine Carcinoma: Diagnostic, Prognostic and Therapeutic Issues

Abstract: Large cell neuroendocrine carcinoma (LCNEC)of the urinary tract is a high-grade neuroendocrine tumor with distinct pathological features, usually portending an aggressive clinical behavior in comparison to conventional urothelial carcinoma. Due to its low prevalence, little is known about its clinical management and there is no current standard of care. The aim of this review was to summarize the current knowledge about LCNEC of the bladder, ureter and kidney, with relevance to diagnostic, prognostic and thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 76 publications
1
41
0
Order By: Relevance
“…According to the literature reports, CD56, synapthophysin, and chromogranin are expressed in most cases (100%, 92.6%, and 85.2%, respectively). 7 In our cohort, all LCNEC expressed at least 1 NE marker. LCNEC is a high proliferating tumor, with a Ki-67 index of up to 100%; however, a Ki-67 index of >40% has been shown to be 80% sensitive and 86% specific in distinguishing LCNEC and UC, which usually features a Ki-67 proliferation rate as high as 25%.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…According to the literature reports, CD56, synapthophysin, and chromogranin are expressed in most cases (100%, 92.6%, and 85.2%, respectively). 7 In our cohort, all LCNEC expressed at least 1 NE marker. LCNEC is a high proliferating tumor, with a Ki-67 index of up to 100%; however, a Ki-67 index of >40% has been shown to be 80% sensitive and 86% specific in distinguishing LCNEC and UC, which usually features a Ki-67 proliferation rate as high as 25%.…”
Section: Discussionmentioning
confidence: 66%
“… 9 28 , 34 Most clinical studies have analyzed both SmCCs and LCNECs, the latter comprising a small amount of the whole case series, and reported similar survival and cancer-specific mortality rates in LCNEC compared with SmCC, ranging from <1 year for advanced disease to >2 years for early disease. 7 , 12 , 15 , 16 Bhatt et al 10 reported a 5-year survival rate of 17% for their study population, which consisted of 14 SmCCs and only 4 LCNECs. Although our analysis is limited by comparison across study cohorts and our inability to conduct a multivariable analysis due to small sample size, it is the largest series of LCNEC in the literature and it suggests that the outcome of LCNEC may be worse than SmCC, especially for metastatic patients.…”
Section: Discussionmentioning
confidence: 90%
“…A cisplatin-based chemotherapy consisted the base of the treatment strategies through literature. A multimodal therapeutic approach, using the combination of chemotherapy, radiotherapy, and radical or partial surgeries, has been reported [ 3 , 4 , 25 , 27 ]. Dowd et al reported after the treatment by surgical resection and adjuvant chemotherapy and radiotherapy, no recurrence at one year [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Microscopically, SmCC shows sheets, nests, or trabecular growth patterns, with tumor cells having scant cytoplasm, nuclear molding, crowding, and lack of prominent nucleoli with chromatin pattern referred to as powdery or salt-and-pepper. 2,11,12 The histopathologic pattern of LCNEC shows sheet-like, palisading, trabecular, and an organoid nested growth pattern. The tumor cells have abundant cytoplasm, coarsely granular nuclei, and occasional prominent nucleoli.…”
mentioning
confidence: 99%
“…Currently, by World Health Organization (WHO) criteria, the diagnosis of HGNEC of the lung is similar to those present in other sites, including the urinary bladder, and it depends entirely on histopathology, immunochemistry, and ultrastructural features 4,11. Microscopically, SmCC shows sheets, nests, or trabecular growth patterns, with tumor cells having scant cytoplasm, nuclear molding, crowding, and lack of prominent nucleoli with chromatin pattern referred to as powdery or salt-and-pepper 2,11,12. The histopathologic pattern of LCNEC shows sheet-like, palisading, trabecular, and an organoid nested growth pattern.…”
mentioning
confidence: 99%